Partnership in the Classroom: Engaging Students Through Inclusive Student-Teacher Relationships to Advance Social Justice - Tanya Lubicz-Nawrocka; Xiuxiu Bao (Social Sciences, 2025)
Student-teacher relationships matter in creating inclusive student engagement opportunities in higher education. Student engagement is a wide-ranging topic, and much of the existing literature discusses student course representation (where student leaders gather feedback and work with staff to enhance the quality of courses) and curriculum co-creation (where students and teachers partner in decision-making regarding aspects of a course) as two distinct approaches. However, there is a notable paucity of prior empirical research comparing the ways that student representation and curriculum co-creation can lead to different forms of relationship-building. Therefore, this qualitative study first examined student course representatives’ and co-creators’ perceptions of effective student-teacher relationships in courses, followed by an analysis of the differences in those relationships between teachers and (a) course representatives and (b) curriculum co-creators. We identified five elements of effective student-teacher relationships within the classroom context that help students feel included, connected, respected, valued, and inspired. We found that different communication structures inherent in course representation and curriculum co-creation yielded distinct contributions and risks in building inclusive student-teacher relationships. To deepen understanding of inclusive student engagement, we explore opportunities to enhance these relationships and work towards meaningful partnerships between students and teachers that can advance social justice.